Genetic variation and genome-wide association analysis of nitrogen use efficiency-related traits under combined heat and nitrogen-deficient stress in an Aegilops tauschii-derived wheat population - Emam, Amir Ibrahim Ismail; Tahir, Izzat Sidahmed Ali; Kamal, Nasrein Mohamed; Gorafi, Yasir Serag Alnor; Tsujimoto, Hisashi; Ishii, Takayoshi (Frontiers in Plant Science, 2025)
Heat stress and nitrogen (N) deficiency increasingly limit global wheat (Triticum aestivum L.) yields, highlighting the need to improve nitrogen use efficiency (NUE) under combined stresses for sustainable production. We assessed 145 multiple-synthetic-derivative (MSD) lines, carrying alleles from diverse Ae. tauschii, crossed and backcrossed into ‘Norin 61’, together with three checks across six field environments combining heat stress and either optimal (86 kg N ha-¹; HS-HN) or zero (HS-LN) N supply in central Sudan. Eighteen agronomic and physiological traits were recorded, and best linear unbiased estimates were used for genome-wide association analysis (GWAS) with 31,362 high-quality DArTseq and GRAS-Di markers. HS-LN reduced mean grain yield (GY) and grain N uptake (GNUp) by 14% and 28%, respectively, but increased thousand-kernel weight and harvest index, indicating resource re-allocation to grain filling. The MSD lines showed wide variation, and some lines maintained high GY under either HS-HN (e.g., MSD053 and MSD450) or HS-LN (e.g., MSD192 and MSD383). The MSD lines MSD026, MSD181, and MSD485 ranked among the top five for GY under HS-LN, HS-HN conditions, and across the six environments. GWAS identified 34 marker-trait associations (MTAs) on 12 chromosomes; 62% resided in the D subgenome. A pleiotropic locus on 5A (rs987242) affected grain growth rate and GY, whereas a novel locus on 3D (rs1071033) explained 88% of the variation in GNUp relative performance. Candidate genes included mitogen-activated protein kinases, DELLA (Rht-1), MADS-box, and DnaJ homologues linked to stress signaling or N metabolism. Our results uncover genetic variants and germplasm that enhance NUE and yield stability under concurrent heat and N stress, providing immediately deployable resources for climate-resilient wheat breeding.